Radiation use efficiency of alfalfa radiation use efficiency of alfalfa‐tall fescue mixtures in a temperate humid area - Scheneiter, Jorge Omar (2008)
Alfalfa (Medicago sativa L .) and tall fescue ( Festuca arundinacea Screb .) have ecotypes with different responses to temperature . Hypothetically, combination of germplasm with different patterns of seasonal growth might exhibit advantages in radiation use efficiency ( RUEfa ). In the Humid Pampa region , grass is the main species in these mixtures in winter . However , seasonal transition is crucial to study mechanisms of dry matter accumulation in mixtures with cultivars of different temperature responses . In this work , RUEfa of two alfalfa‐tall fescue mixtures are presented.